2015
DOI: 10.1017/s0967199415000489
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics and their intracellular traffic in porcine oocytes

Abstract: SummaryMeiotic maturation of oocytes requires a variety of ATP-dependent reactions, such as germinal vesicle breakdown, spindle formation, and rearrangement of plasma membrane structure, which is required for fertilization. Mitochondria are accordingly expected be localized to subcellular sites of energy utilization. Although microtubule-dependent cellular traffic for mitochondria has been studied extensively in cultured neuronal (and some other somatic) cells, the molecular mechanism of their dynamics in mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…After PC administration, 88.95% of oocytes were evenly distributed around mitochondria, which was similar to the oocytes in control (Figure 6C and 6D , Table S6-2 ). Mitochondrial distribution is a cytoskeleton-dependent intracellular traffic behavior [ 41 ]. The distribution of mitochondria in oocytes determines spindle translocation [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After PC administration, 88.95% of oocytes were evenly distributed around mitochondria, which was similar to the oocytes in control (Figure 6C and 6D , Table S6-2 ). Mitochondrial distribution is a cytoskeleton-dependent intracellular traffic behavior [ 41 ]. The distribution of mitochondria in oocytes determines spindle translocation [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that PC improved mitochondrial distribution mainly via its inhibition of ROS. A previous study reported that mitochondrial distribution is a cytoskeleton-dependent intracellular traffic behavior that relies on microtubule organization [ 41 ]. The disruption of mitochondrial distribution is therefore a consequence of malfunctioned cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…However, obesity induces an abnormal distribution pattern for mitochondria in oocytes, and increases compensatory responses to oxidative stress, mitochondrial biogenesis, and mtDNA replication, which eventually leads to mitochondrial dysfunction (Grindler and Moley, 2013). Previous studies have reported that the distribution of mitochondria is cytoskeleton-dependent and depends on microtubule organization (Yamochi et al, 2016). Therefore, the disruption in the distribution of mitochondria is likely the result of cytoskeletal disorders in HFD mice (Islam et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, melatonin supplementation significantly increased mtDNA copy number in MII-stage oocyte and influenced the degree of mitochondria granulated clustering ( Figure 4 A,B). Though the mitochondria distribution is a dynamic process [ 44 ], it is an important indicator of oocyte quality. A uniform, granulated distribution of active mitochondria in oocyte maturation and the early embryo specific period is necessary [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%